Efficient biodegradation of organic matter using a thermophilic bacterium and development of a cost-effective culture medium for industrial use. Issue 6 (11th May 2020) - Cai, Yiting; Huang, Yining; Huang, Xuedi; Fan, Zhuoying; Yu, Ting
Abstract: Microorganisms with efficient organic matter degradation ability are essential for organic waste treatment. In this study, a thermophilic bacterium, Bacillus thermoliquefaciens, was identified to have excellent cellulase, amylase, and protease activity, and provided efficient degradation of food waste. This is the first report on the organic matter degradation potential of B. thermoliquefaciens . Using a "one-variable-at-a-time" approach and response surface methodology, the optimal culture conditions for B. thermoliquefaciens were determined to be a 5% inoculation level, 50 °C culture temperature, 25 mL filling volumes in 250 mL flasks, and 180 rpm shaking for 24 h. The optimized medium was formulated as 1 g Na2 HPO4, 1 g KH2 PO4, 0.05 g MgSO4, 3 g NaCl, 0.05 g CaCl2, 11.44 g wheat bran powder, 4.92 g soybean meal, and 1 L distilled water at pH 7.12. The maximum biomass attained was 1.57 ± 0.153 × 10 9 CFU/mL. The cost of this medium was 4.18 times less than that before optimization. This promising result lays a foundation for future industrial application of this bacterium to the degradation of organic waste.